Gambaran Kejadian Efek Samping Obat Antibiotik Golongan Sefalosporin Pada Pasien Rawat Inap di Rumah Sakit “X” Surakarta Periode 2024 - Brianne Corina; Yane Dila Keswara; Francisca Tri Wituningtyas (Jurnal Farmasi Indonesia, 2025)
In the use of cephalosporin antibiotics, it is necessary to be aware of the side effects on patients. One of the effects of drug side effects on patients is the emergence of new diseases. This study is a descriptive observational study with data collection using a retrospective method to determine the description of the occurrence of side effects of cephalosporin antibiotic drugs. The results of this study were 15 patients who experienced side effects of the drug consisting of 6 male patients (40%) and 9 female patients (60%). Ceftriaxone is the drug that most often causes side effects (33.33%). The most common form of manifestation is shortness of breath accompanied by swelling and itching (26.67%). The end of the side effects of the drug is cured (93.33%). Inj Dexamethasone 5 mg (iv) and inj Diphenhydramine 10 mg (iv) (33.33%) are drugs that are often used to overcome side effects. The highest naranjo score results are on a scale of 7 or probable (60%). These results indicate that the use of cephalosporin antibiotics can cause side effects of the drug.